Superior Vena Cava Syndrome. From the Bronchus to the Vessel. Issue 2 (1997) - Witt, C.; Schmidt, B.; Borges, A. C.; Doerffel, W.; Baumann, G.; Romaniuk, P.
Abstract : This paper addresses the diagnosis and management of superior vena cava syndrome (SVCS) due to malignant intrathoracic tumours. Diagnosis of SVCS is usually established by bedside examination. Chest X-ray and computed tomography may be helpful, but the cavography remains the "gold-standard". Other imaging techniques (MRI, nuclear flow studies) are more of scientific interest. Bronchoscopy helps to evaluate the risk of pulmonary complications and endoscopic procedures often lead to histological findings. In the treatment of malignant SVCS surgery, radiotherapy, and chemotherapy have been successfully used. The placement of a vascular stent might be an additional or alternative possibility. There are no conclusive indication criteria and no conclusive regimen concerning post-stenting anticoagulation. From all reported results and published papers we draw the conclusion that the immediate effects of stent implantation and the long-term results of tumour-specific therapy are complementary to one another. The stent dilates the local venous stenosis while tumour-specific therapy has a general effect on the vascular and respiratory situation in a multi-therapy concept.